Risk Factors and Mental Health Status in Patients With Non-Tuberculous Mycobacterial Lung Disease: A Single Center Retrospective Study - Zhao, Zhangyan; Hu, Huiliang; Wang, Mei; Li, Feng; Tang, Haicheng (Frontiers in Public Health, 2022)
According to the existing data, the incidence and prevalence of nontuberculous mycobacteria (NTM) are increasing worldwide. The risk factors and mental health status of patients with NTM lung disease are important and deserve our attention. A total of 180 patients with NTM lung disease hospitalized from January 2018 to December 2021 were selected as the NTM group, and 90 patients with nonsevere community-acquired pneumonia (CAP) who were hospitalized during the same period were selected as the control group. The Symptom Checklist-90 (SCL-90) was used to assess the mental health status of the patients. The data were analysed using descriptive statistics, logistic regression, and receiver operating characteristic (ROC) curves. There were no significant differences in age, sex, marital status or smoking history between the two groups (P>0.05), but there were significant differences in educational level, underlying diseases, occupation, living environment and BMI (P < 0.01). According to the classification of basic diseases, bronchiectasis was found in 82 (45.6%), followed by hypertension in 66 (36.7%) and chronic obstructive pulmonary disease (COPD) in 39 (21.7%). The NTM strains were identified M. intercelleulare caused 41 cases (22.8%), followed by M. avium and M. gordonae, each with 35 cases (19.4%), and M. abscessus with 32 cases (17.8%). The SCL-90 found that 160 (88.9%) of 180 patients with NTM lung disease had developed mental health problems, among which the four highest scoring factors were anxiety (ANX: 29.4%), depression (DEPR: 18.8%), sleep and diet (SD: 16.9%) and somatization (SOM: 11.3%). Through multivariate logistic regression analysis, it was found that educational level, underlying diseases, living environment and BMI were independent risk factors for the occurrence of NTM lung disease (P < 0.01). The Hosmer-Lemeshow test was used to check the model fitness. The receiver operating characteristic (ROC) curve showed that the area under the curve was 0.896, the sensitivity was 83.3%, and the specificity was 85.6%. Patients with NTM lung disease have many risk factors and prominent mental health problems that may require interventions during the process of clinical diagnosis and treatment.